(3JNWjW hQbGHI GdJNRjf (B/s - (3MSjf, LGSe fGUQs; (3GdfLGQ, UHGM eLjOs ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2008)
(3GdebOeI(B- (3GdHGH GdChd(B: (3JNWjW GdNRjf(B: (3GdaUd GdChd(B: (3eaghe GdNRjf hCgejJg(B: (3eGPG jYfj GdNRjf?(B:(3CgejI GdNRjf(B:(3CfhGY GdNRjf(B:(3CgOGa hahGFO JNWjW GdNRjf(B:(3GdaUd GdKGfj(B: (3eaGgje CSGSjI aj eLGd JNWjW GdNRjf(B: (3JcGdja GdNRjf(B:(3JcGdja GdWdH(B:(3eYOd GdNRjf(B:(3eYOd GdGSJgdGc(B:(3GdaUd GdKGdK(B: (3JbOjQ GdWdH Ydi GdehGO GdJNRjfjI(B: (3CSdhH GdNHQI GdTNUjI(B:(3GdSdGSd GdRefjI(B:(3CSdhH GdeQHYGJ GdUZQi(B:(3eYGed GdGQJHGW(B:(3GdaUd GdQGHY(B: (3GdJNWjW GdYdej dTQGA GdGMJjGLGJ ef GdehGO aj MGdI GdGSJgdGc GdefJXe(B: (3CUfGa GdNRjf(B:(3cejI GdWdH GdGbJUGOjI(B:(3TQGA GdGMJjGLGJ GdBfjI hGdeaGVdI Hjf YQhV GdehQOjf(B:(3GdaUd GdNGeS(B: (3GdJNWjW GdYdej ddNRjf aj MGdI GdGSJgdGc GdeJZjQ(B: (3YfUQ GdeNGWQI aj JNWjW GdNRjf(B:(3eUGOQ YOe GdJCcO aj JNWjW GdNRjf(B:(3hSGFd GdJZdH Ydi MGdI YOe GdJCcO aj JNWjW GdNRjf(B:(3GdaUd GdSGOS(B: (3GdJNWjW dHhGbj heNdaGJ GdEfJGL hGdNRjf hGdJNWjW dbWY GdZjGQ(B: (3eUGOQ GdeNdaGJ(B:(3GdJNWjW dHhGbj heNdaGJ GdEfJGL(B:(3GdJNWjW dbWY GdZjGQ (B((3GdCOhGJ GdGMJjGWjI(B):(3GdaUd GdSGHY(B: (3JNWjW GdGMJjGLGJ ef GdehGO(B: (3GdJYQja HJNWjW GdGMJjGLGJ ef GdehGO(B:(3eONdGJ fXGe JNWjW GdGMJjGLGJ ef GdehGO(B:(3eNQLGJ JNWjW GMJjGLGJ GdehGO(B:(3CSdhH GdJNWjW ddGMJjGLGJ ef GdehGO(B:(3CSGdjH JbOjQ MLe GdWdHjI(B- (3GdHGH GdKGfj(B: (3GdQbGHI Ydi GdNRjf(B: (3GdaUd GdKGef(B: (3eaGgje aj GdQbGHI Ydi GdNRjf(B: (3eaghe CgejIGdQbGHI Ydi GdNRjf(B:(3CgOGa hebheGJ GdQbGHI Ydi GdNRjf(B:(3eLGdGJ GdQbGHI Ydi GdNRjf(B:(3NWhGJ GdQbGHI Ydi GdNRjf(B:(3eSJdReGJ GdQbGHI GdaYGdI Ydi GdNRjf(B:(3GdaUd GdJGSY(B: (3fWGb hCSGSjGJ eQGbHI GdNRjf(B: (3GdJMdjd GdKdGKj (B((3C, H, L(B):(3GdSjGSGJ GdCSGSjI deQGbHI GdNRjf(B:(3CSS GNJjGQ GdfXGe GdefGSH(B:(3GdaUd GdYGTQ(B: (3COhGJGdQbGHI Ydi GdNRjf(B: (3GdLQO(B:(3GdehGRfI GdJbOjQjI(B:(3eSJhjGJ GdNRjf(B:(3GdJbGQjQ(B:(3GdaUd GdMGOj YTQ(B: (3GSJNOGe GdMGSHGJ GdEdcJQhfjI aj GdQbGHI Ydi GdNRjf(B: (3eaghe hCgejI GdQbGHI GdBdjI Ydi GdNRjf(B:(3eYhbGJ GSJNOGe fXGe GdQbGHI GdBdj aj efTBJfG(B:(3fXGe GdQbGHI Ydi GdNRjf HGSJNOGe GdMGSHGJ GdEdcJQhfjI(B.s
(3HjHdjhZQGajG U(B.437s
Keywords: (3GdJNWjWs; (3GdQbGHIs; (3GdeNGRfs; (3GdeNRhf (B-(3eQGbHIs